The most mentioned neuroimaging articles in online media: a bibliometric analysis of the top 100 articles with the highest Altmetric Attention Scores. (December 2019) - Kim, Eun Soo; Yoon, Dae Young; Kim, Hye Jeong; Lee, Kwanseop; Kim, Yerim; Bae, Jong Seok; Lee, Ju-Hun
Background: Alternative metrics (Altmetrics) based on mentions in online media is a new tool that can help identify articles that have the most influence on diverse public audiences. Purpose: To determine the 100 most mentioned articles in the field of neuroimaging and to analyze their characteristics. Material and Methods: We selected the 668 journals that were considered to potentially publish neuroimaging articles. Using the Altmetric.com search tool, we identified the 100 most mentioned neuroimaging articles based on the highest Altmetric Attention Scores (AAS) within selected journals. Each article was evaluated for several characteristics including AAS, number of citations, journal title, impact factor of journal, year of publication, authorship, country, type of document, disease entity, and imaging technique. Results: The AAS for the top 100 articles were in the range of 145–1467. Frontiers in Human Neuroscience published the largest number of articles (n = 9), followed by Radiology (n = 8) and Neurology (n = 8). All articles were published during 2006–2018, with 56% of articles being published in 2016–2018. The majority of articles originated from the United States (n = 56), were original articles (n = 81), covered normal population (n = 67), and used functional magnetic resonance imaging (n = 56). Sasaki was the most prolific, authoring three of the most mentioned neuroimaging articles. Conclusion: This study presents a detailed list of the 100 most mentioned neuroimaging articles in online media, thus providing useful information on the dissemination of neuroimaging research to the general public.